The Lichens (Late Pleistocene hunter-gatherer adaptations to tundra environments of North Baikal Siberia) project: aims and first results. - Henry, Auréade; Gauvrit-Roux, Eugenie; Jacquier, Jérémie; Mallol, Carolina; Rué, Mathieu; Aleksei, Teten’kin (CCSD, 2019)
International audience